Dergi Reklamlarında Spor Ünlüsü Kullanımı: GQ Türkiye Örneği - Katırcı, Hakan; Yüce, Arif (The Turkish Online Journal of Design Art and Communication, 2016)
Using celebrities in magazine ads is a popular advertising technique around the world. The purpose of this paper is to analyse sport celebrity endorsements in GQ Turkey. A content analysis approach is used to analyse ads. The findings showed that sport celebrity endorsements are use 3,29% ratio in all ads. However any woman sport celebrity endorsement is used. Generally the football players are used in sport celebrity endorsements.
Keywords: Dergi; Reklam; Ünlü; Dergi Reklamı; Spor Ünlüsü; Magazine; Advertisement; Celebrity; Magazine Advertisement; Sport Celebrity